Associations of genetic variations in the OCX-32 gene with egg production traits in Korean native chickens - LEE, JI-YEON; CHOI, SO-YOUNG; SINGH, NARESH KUMAR; YANG, SONG-YI; HONG, MIN-WOOK; JEONG, DONG KEE; HONG, YEONG HO; LEE, SUNG-JIN (The Indian Journal of Animal Sciences, 2017)
The present study was undertaken to find out novel single nucleotide polymorphism (SNPs) and to analyze the association between SNPs of OCX-32 gene and egg production traits, in the four Korean native chicken breeds (Ogol, black, gray, and white). Twenty-one variations (16 SNPs and 5 INDELs) in the intronic region of the OCX-32 gene were detected, including new 9 variants (1500T>A, 1504A>G, 1658A>G, 1668A>T, 1821A>C, 1234 del A, ins CTT, ins TTC, and 1681 del T) in the chicken population (n=120). Fifteen variations (1346A>G, 1373G>A, 1399T>C, 1446C>G, 1500T>A, 1504A>G, 1522G>A, 1530T>A, 1563G>A, 1668A>T, 1743G>T, 1772T>A, 1821A>C, ins TTC, and ins TCT) showed significant association with egg production ratio, weight and age in the chickens. Conclusively, the result obtained suggested that SNPs and INDELs of the OCX-32 gene might be useful as genetic markers for egg production traits in breeding program of the Korean native chicken.